Variant Alleles of the ESR1, PPARG, HMGA2, and MTHFR Genes Are Associated With Polycystic Ovary Syndrome Risk in a Chinese Population: A Case-Control Study - Jiao, Xianting; Chen, Weiwei; Zhang, Jun; Wang, Weiye; Song, Junjiao; Chen, Dan; Zhu, Wenting; Shi, Yuhua; Yu, Xiaodan (Frontiers in Endocrinology, 2018)
Polycystic ovary syndrome (PCOS) is the most common endocrinopathy in women of reproductive age, with a prevalence of 6–8%. Although the etiology of PCOS has been investigated extensively, the association between genetic predisposition and PCOS risk is largely unknown. In this study, we genotyped 63 SNPs in 10 genes among 361 PCOS patients and 331 healthy controls in a Chinese Han population. The following variant alleles were significantly associated with decreased PCOS risk: ESR1 rs9340799 (P = 0.000), PPARG rs709154 (P = 0.013), and rs1151996 (P = 0.013), HMGA2 rs2272046 (P = 0.000), MTHFR rs1801133 (P = 0.000). Accordingly, the following genotypes at various loci were associated with reduced PCOS risk: GA genotype at rs9340799 (P < 0.0001) in ESR1, TA genotype at rs709154(P < 0.0001) in PPARG and CA genotype at rs2272046 (P < 0.0001) in HMGA2. Moreover, GA genotype at rs1999805 (P = 0.013) in ESR1 and TT genotype at rs1801133 in MTHFR (P < 0.0001) correlated with elevated PCOS risk. Furthermore, haplotype analysis revealed significant differences in haplotype distributions of CYP11A1, ESR2 and PPARG gene between cases and controls. In addition to confirming that ESR1 rs9340799, HMGA2 rs2272046 and MTHFR rs1801133 are related to the risk of PCOS, these findings also provide the first evidence that PPARG rs709154 and ESR1 rs1999805 are significantly associated with PCOS risk in a Chinese population. Further functional studies are warranted to elucidate the underlying biological mechanisms.